Efeito da atmosfera controlada estática e dinâmica nos metabólitos voláteis de frutos intactos e suco de maçãs ‘Fuji Kiku’ e ‘Granny Smith’ - Donadel, Jossiê Zamperetti (2019)
Volatile compounds (VCs) play an important role in the postharvest quality of apples. Storage alternatives that favor the maintenance of quality and formation of odoriferous impact VCs characteristic of fruits have been intensively studied. However, the production of these compounds related to the storage of apples in dynamic controlled atmosphere monitored by the respiratory quotient (DCA-RQ) is still incipient. In view of this, this thesis is composed of 3 scientific articles that resulted from the works whose objectives were: 1) to compare the volatile compounds from the headspace of the storage chambers, fruit headspace in the shelf life (1 and 7 days) and the juice extracted from apple 'Fuji Kiku' after 7 days shelf life at 20 °C; 2) to evaluate the effect of the application of 1-MCP on the volatile composition of Granny Smith apples subjected to storage under conventional static controlled atmosphere (SCA) and dynamic (DCA-CF and DCA-RQ) and 3) to evaluate α-farnesene, 6-methyl-5-hepten-2-one, 6-methyl-5-hepten-2-ol, ethanol concentration, and internal ethylene concentration (IEC) and correlate their emissions with the occurrence of superficial scald (SS). In relation to ‗Fuji Kiku‘ apples, in the storage chambers, ethyl linear chain esters were detected mainly in DCA-RQ1.5, while acetaldehyde and (E)-2-hexenal were more abundant in DCA-CF. At seven days of shelf life, fermentative metabolic compounds had reduced emissions given the opening time of the chamber, while there were higher emissions of branched chain esters, especially ethyl 2-methyl butanoate in DCA-RQ1.5. The correlation was high and positive between the VCs present in the juice and those emitted by the fruit during seven days of shelf life, demonstrating that the concentration of VCs in extracted juice can be used to estimate the emissions from whole fruit. For 'Granny Smith' apples, fruits stored after 9 months at 1.5 ° C plus 7 days at 20 ° C in ACD-QR1.5, treated with 625 nL L-¹ of 1-methylcyclopropene (1-MCP) showed higher concentrations of fermentative metabolism compounds, while higher concentrations of aroma impact esters were found in storage in ACD-QR 1.5 without 1-MCP application. Thus, this condition provided higher emissions of VC that characterize odor and aroma, even with lower ethylene concentration, respiratory rate and ACC oxidase activity in relation to CA, besides maintaining the total soluble solids content, acidity, flesh firmness and fruit health equivalent to fruits treated with 1-MCP. In addition to maintaining the total soluble solids content, acidity, flesh firmness and fruit healthiness. In addition, higher concentrations of α-farnesene and its oxidation metabolites were negatively correlated with SS in DCA-RQ. This is likely due to the higher levels of ethanol which in turn reduced CIE in fruit stored under this condition having an inhibitory effect on SS incidence even when α-farnesene, 6-methyl-5-hepten-2-one, and 6-methyl-5-hepten-2-ol accumulate. From the obtained results, the concentration of VCs in the juice can be evaluated to estimate the emission of VCs from intact fruits, since there was a strong correlation between the VCs in the juice and those emitted by the fruit during seven days of life. In DCA-RQ1.5 there was an apparent increase in important VCs such as 'Fuji Kiku' and ‗Granny Smith‘odor and aroma characteristic ethyl esters, ensuring better market quality. Additionally, DCA-RQ1.5 condition reduced the occurrence of superficial scald in 'Granny smith' apples after prolonged storage.DCA-RQ1.5 offers an effective and cheaper alternative without the use of 1-MCP to maintain apple fruit quality in terms of odor and aroma and reduction of physiological disorders after several months of refrigerated storage.